Enhancing students’ academic motivation and higher-order thinking skills through OBE-based hybrid learning model / Irwan Mahazir Ismail ... [et al.] - Ismail, Irwan Mahazir; Zheng, Zheng; Wang, Hanxu; Abdul Rahim, Azwin Arif (Universiti Teknologi MARA, Kedah, 2023)
Exam-oriented education in China results in the fact that with too much reliance on traditional teaching methods, students have less need for critical or creative thinking when rote memorization has penetrated the whole course. This study analyzes the delivery mode of Fundamental Computer Application hybrid learning courses using outcome-based education (OBE) instructions. It also explores the relationship between elements of OBE instructions and students’ academic motivation and higher-order thinking skills (HOTs) under the hybrid OBE-based curriculum at Jitang College, North China University of Science and Technology. Using stratified sampling, twenty of the college’s 150 first-grade students became the respondents for the survey. These undergraduates registered for hybrid lectures that are mandatory for them for one semester. Three instruments were adapted, and Cronbach’s α value of the hybrid learning questionnaire, students’ motivation level questionnaire and level of students’ HOTs questionnaire indicated good reliability for the study. The data showed the students’ high agreement with the hybrid courses, and the four elements in the OBE instruction have significant relevance to the student’s motivation and HOTs levels. Besides, all the OBE-based hybrid learning elements (real need, clear content, interrelated outcomes and actual output) reported a significant positive correlation with students’ academic motivation and HOTs levels. The results promote positive changes in conducting high-quality FCA hybrid courses and the potentialities of the hybrid OBE-based learning model on students’ motivation and HOTs levels.